ANALISIS SISTEM ANTRIAN DAN HUBUNGANNYA DENGAN PELAYANAN KASSA PADA PT. CARREFOUR CITRA GARDEN MEDAN - Simanihuruk, Peran (UNIKA Santo Thomas, 2010)
PT. Carrefour Citra Garden Medan engaged in the retail market various products, such as fresh, bazaar, textile, and grocery applane. The number of customers who shop from January to December 2010 fluctuates every month and long lines occurred in August when the feast of Eid al-Fitr and December when the Christmas and New Year's Eve. From the description, formulated the following research problem: